Penentuan Penerima Bantuan Program Kami Peduli Dengan Metode SMART - Cindy Agustina (JISTI: Jurnal Ilmu Komputer, Sistem Informasi dan Teknologi Informasi, 2025)
PT. Aquafarm Nusantara, is a government solution to improve the welfare and economic equality of the community through the development of capital access and capacity building programs. To support the growth of those who want to start a business or who have started a business, thereby improving their business. The SMART (Simple Multi-Attribute Rating Technique) method is one of the methods used to solve multi-criteria decision-making problems. This method is used to solve problems in choosing the best alternative from several existing alternatives, using several given criteria. Based on the explanation of the problem above, a decision support system was built with the SMART (Simple Multi-Attribute Rating Technique) method. To overcome problems related to determining whether assistance can meet the requirements to help prospective assistance, it is possible to analyze the process that plays a determining role in selecting assistance at PT. Aquafarm using the SMART (Simple Multi-Attribute Rating Technique) method. From the results of the study, it was found that alternative A1 was said to be feasible with a value of 0.7.